الروايات الإسرائيلية في تيسير التفسير للشيخ اطْفَيِّش وآثارها : دراسة تحليلية لنماذج مختارة - مسروري، خالد بن حمد بن محمد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This research discusses the Israeli narratives in the book of Taysser Al-Tafsir by Sheikh Atfish. It aims to introduce Sheikh Atfish's biography and his scientific contribution, especially in the area of interpretation. Next, this research discusses Taysser Al-Tafsir and extrapolates and analyzing the opinion of Sheikh Atfish regarding a sample of Israeli narratives. The study compares, in some cases, this opinion with his succeeding and preceding peers. The study also discusses the ideological and moral negative-effect of these narratives. The researcher used two main approaches. The first is an inductive approach, in which the researcher reviewed the concept of Israeli narratives, its origin, its development, and its relation to the interpretation books, and found a sample of unanimous Israeli narratives in Taysser Al-Tafsir. The second is an analytical approach, in which the researcher analyzed these narratives and study the extent of their logical and textual conflict with Quran and Sunnah, this was paralleled with highlighting Sheikh Atfish's comments pertaining to these narratives and clarifying the ideological and moral impact of such narratives. One of the most important findings of this research is that Sheikh Atefish took the approach of those who permit the use of Israeli narratives in interpretation. However, he did not quote such narratives much in his book, and he gave comments if these narratives contradict the principles and teachings of Islam.